Penerapan Smart Contract dalam Industri Konstruksi di Indonesia: Potensi dan Tantangan Hukum - Valentino, Christianto Youstra; Azheri, Busyra; Oktavia, Sri (Nagari Law Review, 2023)
Technological advancements in Indonesia's Construction have initiated a digital transformation in the sector. The necessity of incorporating automated systems in contract performance to meet future digital needs has become increasingly apparent. This paper presents to spearhead research into the possibility of the Indonesian construction industry adopting smart contracts. The chosen research approach is a qualitative scientific methodology involving a systematic review highlighting the benefits and obstacles associated with adopting smart contracts within the construction industry. Further data were collected from construction contract management experts through interview sessions. The findings reveal that the self-execution feature of smart contracts could better distribute risks within a contract. However, the study also uncovers substantial challenges in applying smart contracts, such as their immutability, irreversibility, and vulnerability to human errors. The study concludes that smart contracts are best suited for short-term contracts that do not require variations. Smart contracts could streamline contract management, reducing time and effectively addressing conflicts and disputes during the contract's lifespan. The devised implementation framework holds significance for construction professionals, particularly those involved in contract administration. Incorporating smart contracts into construction could enhance contract administration and management discipline by fostering investment in this emerging technology